THE ROLE OF BELIEFS AND PRACTICES IN HEALTH ON PATIENTS’ COMPLIANCE - Daisy R. Palompon (The Malaysian Journal of Nursing (MJN), 2012)
The degree of influence of traditional beliefs and practices of a person as part of his or her cultural background is indeed a creative molder of a person’s behavior such as attitudes, beliefs and practices regarding health promotion and prevention of illness. This study determined the level of influence of health beliefs and practices on the level of compliance with regard to discharge instructions given to the patients in selected hospitals in Sogod, Southern Leyte, Philippines. Utilizing a co-relational design, thirty respondents were selected by purposive sampling technique. A researcher-made interview schedule was utilized. The compliance behavior of the respondents on medications showed that majority of the respondents were highly and moderately compliant while compliance with out-patient referral showed that majority have poorly complied. Majority of the health beliefs most frequently identified were scientific while the practices were mostly parochial. There was no significant relationship between health beliefs and practices with medication compliance. Significant correlations were shown between health beliefs and practices and out-patient referral compliance. Reasons for non-compliance for medications includes financial constraints and forgetfulness while on out-patient referral, respondents did not comply the follow-up consultation due to the absence of symptoms or due to the suggestions of a faith healer for further management. It is concluded that health beliefs and practices do not influence compliance of medication since it is basically a consideration of individual’s budgetary capacity. It is further concluded that health beliefs and practices significantly influence out-patient referral compliance since it is affected more by the behavioral attributes.